2015
DOI: 10.1007/s00392-014-0799-7
|View full text |Cite
|
Sign up to set email alerts
|

German Heart Report 2013

Abstract: Objectives The 25th German

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 9 publications
3
17
0
2
Order By: Relevance
“…Finally, in AF patients with reduced LVEF and without coronary artery disease, it remains difficult to distinguish between tachymyopathy or early stage DCM even in the presence of enlarged LV diameters . Several variables may lead to impaired LV systolic function, and these could be improved after successful AF ablation. Improved atrial contraction itself may significantly contribute to an improvement in LV systolic function .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in AF patients with reduced LVEF and without coronary artery disease, it remains difficult to distinguish between tachymyopathy or early stage DCM even in the presence of enlarged LV diameters . Several variables may lead to impaired LV systolic function, and these could be improved after successful AF ablation. Improved atrial contraction itself may significantly contribute to an improvement in LV systolic function .…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure is a major and increasing public health problem with a high mortality rate [1][2][3]. Recent reports indicate that hypoalbuminemia is closely associated with extremely poor outcomes in patients with chronic heart failure (CHF) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these two studies, Dvir et al [24] demonstrated no difference between SAVR and TAVR in patients with chronic lung disease, and Onorati et al [25] in patients with Comparative principle (a left) and outcome (a right) from a network meta-analysis comparing percutaneous coronary intervention, coronary bypass surgery and medical therapy as treatment for stable coronary artery disease [16] as well as the current guideline recommendations [15] b. Reproduced with permission ejection fractions below 35 %. Many other studies were published in this field with varying outcomes [26][27][28].…”
Section: Aortic Valve Surgerymentioning
confidence: 96%